2011
DOI: 10.1002/prep.201000114
|View full text |Cite
|
Sign up to set email alerts
|

Production and Sensitivity Evaluation of Nanocrystalline RDX‐based Explosive Compositions

Abstract: The initiation sensitivity of cyclotrimethylenetrinitramine (RDX) was investigated as a function of crystal size. For this study, RDX powders with mean crystal sizes of ca. 200 and 500 nm were prepared by rapid expansion of supercritical solutions (RESS) with carbon dioxide as the solvent. Initiation sensitivity testing to impact, sustained shock, and electrostatic discharge stimuli was performed on uncoated as well as wax-coated specimens. The test data revealed that in a direct comparison to coarser grades t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
51
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 12 publications
4
51
0
Order By: Relevance
“…For nano-ADN recrystallized in ethyl acetate, sensitivity behavior follows the trend observed by Bayat et al on CL-20 [19] and Stepanov et al on RDX [20]. Indeed, nano-ADN is less sensitive to impact with a value measured at 4.5 J but is more sensitive to ESD with a value of 996 mJ ( Table 3).…”
Section: Resultssupporting
confidence: 84%
“…For nano-ADN recrystallized in ethyl acetate, sensitivity behavior follows the trend observed by Bayat et al on CL-20 [19] and Stepanov et al on RDX [20]. Indeed, nano-ADN is less sensitive to impact with a value measured at 4.5 J but is more sensitive to ESD with a value of 996 mJ ( Table 3).…”
Section: Resultssupporting
confidence: 84%
“…However, this trend appears to reverse at sizes in the sub-micron regime. It was recently observed that cyclotrimethylenetrinitramine (RDX) crystals with an average size of 500 nm demonstrated the least shock sensitivity and impact sensitivity compared to both larger and smaller RDX crystals [21]. There seems to be an optimal crystal size of RDX, in the range of hundreds of nanometers, for achieving the lowest sensitivity.…”
Section: Introductionmentioning
confidence: 98%
“…Reducing the size of voids, often achieved through decreasing the crystal size of the HE crystals [20,21], can lower the sensitivity of explosives. Initiation sensitivity of explosives has been observed to decrease as crystal size is reduced, particularly when the size of crystals is above micrometers [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, a milling study was carried out to investigate the impact of the solvent and PVP addition on the HMX particle size. This work may have a significant impact toward the production of large quantities of nanoHMX that can be used to reduce the critical diameter and increase the mechanical strength of energetic formulations [18][19][20].…”
Section: Introductionmentioning
confidence: 99%